PERANCANGAN MODUL PRAKTIKUM PENGOLAHAN SINYAL DIGITAL BERBASIS SOFTWARE - Feri Prayogi Dahlan; Yussa Ananda; Erwin Panggabean (Universitas Harapan Medan, 2019)
The digital signal processing practicum is one of the practicums that must be followed by students of the Electrical Engineering Study Program at Harapan University of Medan, especially students of the Telecommunications Engineering concentration. To support the continuation of practicum activities so that they run well, an alternative model is needed and also as a backup if there is a problem with the actual module when doing the practicum. Alternative models can be designed using the help of software. This study aims to design a model of digital signal processing material using matlab software. In this study, a model design was carried out from the practicum material of digital signal processing by utilizing the graphical user interface (GUI) tool in the Matlab programming language. Then testing is carried out on the model that has been designed, the results of this model design are expected to be a supporting method or backup of the actual experiment. From the test results of the practicum model design, all models that have been designed run well and can be used as simulators for digital signal processing practicum. With this simulator, it will foster students' interest in practicum and increase understanding of the material being practiced